Reversible electrochemical oxidation of sulfur in ionic liquid for high-voltage Al−S batteries - Huan Li (Nature Portfolio, 2021)
The sulfur cathode in metal-sulfur batteries normally undergoes electrochemical reduction to form metal sulfides. Here, the authors demonstrate the electrochemical oxidation of sulfur in ionic liquid for high-voltage aluminium-sulfur batteries.